Incidência de lesões de ombro e dor lombar baixa no centro de referência em saúde do trabalhador (CEREST) de Marília - Bueno, José Julio Rosa (2010)
According to the Ministry of Social Security, occupational diseases are that directly related to employees or to underlying work conditions. The most common are Repetitive Strain Injury or Osteomuscular Disturbances due to function (RSI/OD) responsible for alterations on osteomuscular structures, such as tendons, articulations, muscles, and nerves. This study mapped the claims for occupational diseases (RSI/OD) on the CEREST/Marilia, using the data bank with the physiotherapists. This paper aimed to: select according the data recordings the two most prevalent work pathologies during 2007 and 2008; to describe the physiotherapeutic approach for each situation, as well as the discharge conditions and accompanying pathologies. It was concluded that shoulder and lower back pain were the two most prevalent illness; treatment protocols adopted for each disease were: pulsed-short waves, continuous short waves, interferential current, kinesiotherapy, laser, pulsed ultra-sound, continuous ultra-sound, infra-red, as well as motives for discharge and respective pathologies considered as discharge due to improving, discharge without improvements, and dropout discharges.